Severe fever with thrombocytopenia syndrome with central nervous system symptom onset: a case report and literature review - Dawei Shan; Weibi Chen; Gang Liu; Huimin Zhang; Shuting Chai; Yan Zhang (BMC Neurology, 2024)
Abstract Background Severe fever with thrombocytopenia syndrome (SFTS) is a natural focal disease transmitted mainly by tick bites, and the causative agent is SFTS virus (SFTSV). SFTS can rapidly progress to severe disease, with multiple-organ failure (MOF) manifestations such as shock, respiratory failure, disseminated intravascular coagulation (DIC) and death, but cases of SFTS patients with central nervous system (CNS) symptoms onset and marked persistent involuntary shaking of the perioral area and limbs have rarely been reported. Case presentation A 69-year-old woman with fever and persistent involuntary shaking of the perioral area and limbs was diagnosed with SFTS with CNS symptom onset after metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) and peripheral blood identified SFTSV. The patient developed a cytokine storm and MOF during the course of the disease, and after aggressive antiviral, glucocorticoid, and gamma globulin treatments, her clinical symptoms improved, her laboratory indices returned to normal, and she had a good prognosis. Conclusion This case gives us great insight that when patients with CNS symptoms similar to those of viral encephalitis combined with thrombocytopenia and leukopenia are encountered in the clinic, it is necessary to consider the possibility of SFTS involving the CNS. Testing for SFTSV nucleic acid in CSF and blood (mNGS or polymerase chain reaction (PCR)) should be carried out, especially in critically ill patients, and treatment should be given accordingly.